Mixed M-V-Sb oxides as oxodehydrogenization catalysts - V. F. Tretyakov; R. M. Talyshinsky; E. A. Mamedov; R. G. Rizayev; N. A. Frantsuzova (Тонкие химические технологии, 2010)
The properties of mixed M-V-Sb (M = Ni, Co, Bi, Sn) oxides, supported on aluminum oxide, have been physically characterized and their activities estimated .in dehydrogenation of light paraffins, ethyl benzene and ethanol. The most selective NiVSb catalyst was easily reduced which allowed for proposing of the reduction-oxidation mechanism .The result of kinetic researches has shown that, the concentration of oxygen in the gas phase is the key parameter responsible for dehydrogenation selectivity. To maintain the optimal process conditions, oxygen was distributed along the catalyst layers.